HUKUM KODRAT, PANCASILA DAN ASAS HUKUM DALAM PEMBENTUKAN HUKUM DI INDONESIA - Otong Rosadi (Jurnal Dinamika Hukum, 2010)
Goal of legislation establishment is fair legislation carries out mission of prosperous society. To achieve the goal, process of the establishment has to be based on moral nation as philosophical foundation. For Indonesian people, Pancasila on Preamble of UUD 1945, not only as national goal but also as fundamental basic rule of state, should be the basis of legislation establishment.Keywords: legislation establishment, Pancasila, moral nation, legal principle